Detection of Cronobacter spp. (formerly Enterobacter sakazakii) from medicinal plants and spices in Syria - Mouhammad Belal; Ayman Al-Mariri; Lila Hallab; Ibtesam Hamad (Journal of Infection in Developing Countries)
Introduction: Cronobacter spp. (formerly Enterobacter sakazakii) is an emerging food-borne pathogen that causes severe meningitis, sepsis, and necrotizing enterocolitis in neonates and infants. These infections have been reported from different parts of the world. The epidemiology and reservoir of Cronobacter spp. are still unknown, and most strains have been isolated from clinical specimens and from a variety of foods, including cheese, meat, milk, vegetables, grains, spices, and herbs.